Biomarkers of postharvest resilience: unveiling the role of abscisic acid in table grapes during cold storage - Navarro-Calderón, Ángela; Falagán, Natalia; Terry, Leon A.; Alamar, M. Carmen (Frontiers in Plant Science, 2023)
This is a provisional file, not the final typeset article and for the first time, the spatial distribution of ABA during the senescence of table grapes was profiled; the distal section had three times more ABA and metabolites than the proximal. We demonstrated that senescence processes were initiated after a significant increase in respiration rate (from 1 to 2.8 mL CO2 kg -1 h -1 ), and that ABA could be considered a biomarker for table grapes senescence, since an ABA peak preceded the increase in respiration rate, mould incidence, organic acids, and sucrose hydrolysis during postharvest storage; and coincided with a decrease in berry firmness. These findings are of significant importance for the industry as understanding how ABA regulates both senescence processes and quality changes during postharvest cold storage of tables grapes can improve the consistency and reduce waste and consumer complaints.